Designing ESD-integrated outdoor learning to enhance students' systems thinking skills - Duhita Savira Wardani; Ari Widodo; Ernawulan Syaodih; Muslim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study aimed to develop and examine the feasibility and preliminary effectiveness of an Education for Sustainable Development (ESD)-integrated outdoor learning design to enhance students' systems thinking skills in science classrooms, responding to the urgent need for instructional approaches that address students' limited ability to understand complex sustainability issues at the primary education level. The study employed a Design and Development (D&D) research approach, consisting of needs and context analysis, design development, expert validation, and limited implementation. The study involved 200 elementary school students selected through purposive sampling from public schools representing diverse learning contexts. Research instruments included validation sheets, learning implementation tools, and a systems thinking test. Data were analyzed using descriptive statistics, Percentage Agreement (PA) for reliability, paired difference testing, and N-gain analysis. The results indicated that the developed design, learning worksheets, and instruments were highly valid and reliable. Limited evaluation results indicated a significant improvement in students' systems-thinking skills, with a moderate N-gain score. These findings suggest that ESD-integrated outdoor learning can foster a holistic understanding of sustainability issues. It is recommended that future studies implement large-scale programs and investigate the long-term impacts on sustainability-oriented behaviors.